2010
DOI: 10.1080/00050067.2010.512612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervisor training in Australia: A review of current problems and possible solutions

Abstract: Clinical supervision cuts to the heart of professional psychology training. It is the most expensive single investment of staff time in the training of the psychology practitioner, and it appears to be the single most important contributor to training effectiveness, repaying that investment. Now there are changes afoot internationally which may change its pivotal role. For example, the Psychology Board of Australia has recently proposed that supervisors undergo approved supervisor training; in the USA, a compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 37 publications
6
81
0
2
Order By: Relevance
“…In terms of time and resource investments per trainee, clinical supervision is the most expensive component of professional training within several sub-disciplines in psychology (Gonsalvez & Milne, 2010). Most of this supervision occurs in a one-to-one context in university clinics, external field placements/externships/rotations, or/and in year-long internships (terms differ across countries and disciplines; the broader term 'placement' will be used in the current manuscript).…”
Section: Assessment Of Competencies In Field Placement and Internshipsmentioning
confidence: 99%
“…In terms of time and resource investments per trainee, clinical supervision is the most expensive component of professional training within several sub-disciplines in psychology (Gonsalvez & Milne, 2010). Most of this supervision occurs in a one-to-one context in university clinics, external field placements/externships/rotations, or/and in year-long internships (terms differ across countries and disciplines; the broader term 'placement' will be used in the current manuscript).…”
Section: Assessment Of Competencies In Field Placement and Internshipsmentioning
confidence: 99%
“…The shift has led to assessment of the impact of supervision training (Tebes et al 2011), identifying components of effective supervision (Falender and Shafranske 2008;Kavanagh et al 2008), and defining a lifelong trajectory of professional competence and development Wise et al 2010). This development is not isolated to training in the U.S.; Australia, New Zealand, and the U.K. have developed competencies for psychology practice and supervision (Gonsalvez and Milne 2010) and as discussed earlier, competency-based education and training is found in education, medicine and other professions.…”
Section: Competency-based Clinical Supervision: Its Relevance Today Amentioning
confidence: 94%
“…However, its application in supervisory practice is less frequent than desirable (e.g., Townend et al, 2002) and the criteria supervisors use to formulate their evaluations and the reliability of these evaluations have been poorly researched (Gonsalvez & McLeod, 2008;Gonsalvez & Milne, 2010). The study systematically examined supervisor and peer ratings of assessment competencies demonstrated by clinical psychology trainees, and contributes to a better understanding of factors influencing supervisor-peer evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The study has important implications for how feedback involving supervisors and peers might be managed and for peer supervision models. (Gonsalvez & Milne, 2010). First of all, novice trainees lack both competence and confidence, and have to be supported through phases of misgivings and self-doubt as they deal with high levels of affect and difficult psychological problems (Stoltenberg, Bailey, Cruzan, Hart, & Ukuku, 2014).…”
mentioning
confidence: 99%